Increasing the energy efficiency of parallel manipulators by means of kinematic redundancy and Model Predictive Control - Gómez Ruiz, Andrés (2017)
The use of robotic manipulators in industrial applications is continuously growing. Therefore, the proposal of novel kinematic architectures for robotic manipulators can be a strategy for coping with the required performance of specific tasks. On this matter, the parallel manipulators represent an alternative to fulfill this gap. The objective of this manuscript is to prove that the energy efficiency of parallel manipulators can be increased by the use of kinematic redundancy. Due to the presence of kinematic redundancy, the number of solutions to the inverse kinematics problem become infinite. Hence, a redundancy resolution scheme is required to select a suitable one among the infinite solutions. In this work, a model predictive control (MPC) based method is proposed as redundancy resolution scheme. This proposal is evaluated numerically and experimentally by comparing the energy consumption of non-redundant and kinematically redundant manipulators during the execution of pre-defined tasks. The non-redundant manipulator under study is the planar parallel 3RRR manipulator. This manipulator consists of three identical kinematic chains containing one active revolute joint and two passive revolute joints. Kinematic redundancies were added to the manipulator by including one active prismatic joint in each kinematic chain. In this way, the kinematically redundant manipulator under study is the planar parallel 3PRRR manipulator. By activating or locking the prismatic joints, up to three levels of kinematic redundancy can be evaluated. Numerical kinematic and dynamic models of the manipulators under study were derived not only for their numerical evaluation but also for the derivation of the model-based redundancy resolution scheme. Experimental data was acquired using the prototype built at the Laboratory of Dynamics at São Carlos School of Engineering at University of São Paulo. This experimental data was exploited for assessing the usability of the MPC for deriving a redundancy resolution scheme and for evaluating the impact of several levels of kinematic redundancy on the manipulator\'s energy consumption. Based on this data, one can conclude that MPC can be a suitable alternative for solve redundancy resolution problems and that the redundant parallel manipulators presented a lower energy consumption than the non-redundant one to execute the pre-defined tasks. The rate of reduction on the energy consumption achieved by the redundant manipulators varied between 6% and 60% depending on the task. Nevertheless, the numerical and experimental data presented differences in some particular cases.